Computationally exploring ultrafast molecular ionization - Yu, Youliang (Kansas State University, 2018)
Strong-field ionization plays a central role in molecules interacting with an intense laser field since it is an essential step in high-order harmonic generation thus in attosecond pulse generation and serving as a probe for molecular dynamics through either the sensitivity of ionization to the internuclear separation or the laser-induced electron scattering. Strong-field molecular ionization has been studied both theoretically and experimentally, dominantly through the Born-Oppenheimer approximation and at equilibrium or small reaction distances. We have extended the theoretical studies of molecular ionization to a much broader extent. Specifically, due to the difficulty of treating ionization in Born-Oppenheimer representation especially for molecular dynamics involving strongly-correlated electron-nuclear motion, we have investigated an alternative time-independent--adiabatic hyperspherical--picture for a one-dimensional model of the hydrogen molecule. In the adiabatic hyperspherical representation, all the reaction channels--including ionization--for the hydrogen molecule have been identified in a single set of potential curves, showing the advantage of studying molecular dynamics involving multiple breakup channels coupled with each other. We have thus proposed a good candidate to study strongly-correlated molecular dynamics, such as autoionization and dissociative recombination. Moving to a time-dependent picture by numerically solving the time-dependent Schrödinger equation (TDSE), we have explored two extreme classes of strong-field ionization of hydrogen molecule ion: at large internuclear distances (R>30 a.u.) and for long-wavelength laser fields. Remarkably, we have found strong-field two-center effects in molecular ionization beyond the long-standing one-photon two-center interference as a manifestation of the double-slit interference. In particular, the total ionization probability at large internuclear distances shows strongly symmetry-dependent two-center dynamics in homonuclear diatomic molecules and two-center induced carrier-envelope phase effect in heteronuclear diatomic molecules. Such two-center effects are expected to generalize to other diatomic systems and could potentially be used to explain phenomena in multi-center strong-field physics. Moreover, we have theoretically confirmed, for the first time, the existence of low energy structure in molecular ionization in long-wavelength laser fields by solving the three-dimensional TDSE. Finally, we have performed a pump-probe study of the hydrogen molecular ion where a pump pulse first dissociates the molecule followed by a probe pulse which ionizes the dissociating wave packet, and surprisingly found a pronounced broad ionization peak at large R or large pump-probe delay (~150 fs). Numerically, we have developed and implemented new theoretical frameworks to more accurately and efficiently calculate quantum mechanical processes for small molecules--hydrogen molecule and its ion--which could readily be adapted to heavier diatomic systems.
Keywords: Ultrafast; Strong-field; Molecular dynamicsPhysics